An Econometric Analysis of US Food Expenditure, 1931-1989 - Hendry, D (John Wiley and Sons, 1999)

(untitled)
This paper applies a ‘general-to-specific’ modelling approach to the US annual food expenditure time series in Magnus and Morgan (1995), denoted M–M. It discusses how to model the updated data from Tobin (1950), given the questions M–M seek to have answered.